2022
DOI: 10.1093/mnras/stac2722
|View full text |Cite
|
Sign up to set email alerts
|

Lightning-induced chemistry on tidally-locked Earth-like exoplanets

Abstract: Determining the habitability and interpreting atmospheric spectra of exoplanets requires understanding their atmospheric physics and chemistry. We use a 3-D Coupled Climate-Chemistry Model, the Met Office Unified Model with the UK Chemistry and Aerosols framework, to study the emergence of lightning and its chemical impact on tidally-locked Earth-like exoplanets. We simulate the atmosphere of Proxima Centauri b orbiting in the Habitable Zone of its M-dwarf star, but the results apply to similar M-dwarf orbitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 154 publications
1
15
0
Order By: Relevance
“…Our implementation, and this study are focused on the stratospheric ozone distribution on an 'Earth-like' planet with an initial atmospheric composition similar to modern Earth in a tidally locked orbit of a host M dwarf star, based on ProxCen b. This work has been performed alongside and in close collaboration with that of Braam et al ( 2022 ) who further adapted the UKCA framework, building on the work of Yates et al ( 2020 ), to study the impact of lightning on the tropospheric ozone composition of ProxCen b also using the UM. As we have been using the same GCM and the same planetary configuration, but different chemistry schemes, this has provided a useful environment for testing and developing both of our models.…”
Section: The Unified Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Our implementation, and this study are focused on the stratospheric ozone distribution on an 'Earth-like' planet with an initial atmospheric composition similar to modern Earth in a tidally locked orbit of a host M dwarf star, based on ProxCen b. This work has been performed alongside and in close collaboration with that of Braam et al ( 2022 ) who further adapted the UKCA framework, building on the work of Yates et al ( 2020 ), to study the impact of lightning on the tropospheric ozone composition of ProxCen b also using the UM. As we have been using the same GCM and the same planetary configuration, but different chemistry schemes, this has provided a useful environment for testing and developing both of our models.…”
Section: The Unified Modelmentioning
confidence: 99%
“…The increased rate of photolysis leads to significantly higher abundances of atomic oxygen, which leads to significantly faster growth in ozone through the three-body reaction O 2 + O( 3 P) + M −→ O 3 + M , where M denotes a third body. Braam et al ( 2022 ) used the same spectrum as this work to simulate a similar 'Earth-like' planet as Yates et al ( 2020 ), and found that when compared to Yates et al ( 2020 ) (who used the BT-Settl spectrum) they had significantly higher amounts of ozone. This was due to two factors, the change in spectrum to one which has higher UV increases the amount of ozone significantly, and an impro v ed calculation of photolysis rates as compared to the work done by Yates et al ( 2020 ).…”
Section: Stellar Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The increased rate of photolysis leads to significantly higher abundances of atomic oxygen, which leads to significantly faster growth in ozone through the three-body reaction O 2 + O( 3 P) + M − −− → O 3 + M, where M denotes a third body. Braam et al (2022) used the same spectrum as this work to simulate a similar 'Earth-like' planet as Yates et al (2020), and found that when compared to Yates et al (2020) (who used the BT-Settl spectrum) they had significantly higher amounts of ozone. This was due to two factors, the change in spectrum to one which has higher UV increases the amount of ozone significantly, and an improved calculation of photolysis rates as compared to the work done by Yates et al (2020).…”
Section: Stellar Spectrummentioning
confidence: 99%
“…In reality, to make progress we need a range of approaches. In this work we introduce a new model, complementary in its approach to that of Chen et al (2021) and Braam et al (2022) in examining ozone chemistry in 3D, but are aware that this first step motivates extensive follow-up both in terms of more extensive application of this model, and further development.…”
Section: Future Workmentioning
confidence: 99%